Discovering gender-related uncommon practices for improved nutrition of mothers and children through the Positive Deviance approach in rural Madhya Pradesh, India - Bader, Nadine; Verma, Avani; Milcher, Susanne (Deutsche Gesellschaft für Internationale Zusammenarbeit, 2023)
The aim of the study was to discover uncommon practices among families with well-nourished mothers and young children living in equally low socioeconomic circumstances in rural Madhya Pradesh that lead to improved nutrition outcomes. A positive deviance (PD) inquiry was carried out with 23 families in seven villages, including semi-structured interviews with mothers and other household members and participatory observations. Successful uncommon practices were shortlisted, validated, and reflected upon in terms of feasibility in focus group discussions with fathers, grandparents, mothers, adolescent girls, and Anganwadi workers. Many of the discovered uncommon practices of the families were related to gender, such as supportive fathers undertaking conscious financial planning to ensure good nutrition for mother and child, attaining knowledge about good nutrition, not consuming alcohol, feeding the child in the morning before work, eating together, and joint decision-making (e.g., in family planning). The reflection with community showed willingness for adoption and dissemination of most practices. However, practices related to alcohol consumption and family planning require multiple actions beyond individual level. Hence, prioritization of doable practices needs to be guided by the community. Dialogues with young fathers talking about their children and relationships have potential to enhance their engagement. Enabling Anganwadi workers as frontline workers and part of communities to engage in the promotion of these practices could be a lever toward improved nutrition outcomes but requires strengthening their capacities to interact with male members. The PD approach is a useful tool to identify and promote gender-related uncommon practices driven by the community